Electroacupuncture for the treatment of frozen shoulder: A protocol for systematic review and meta-analysis. Issue 51 (23rd December 2021) - Heo, Jeong-Weon; Jo, Jeong-Hun; Lee, Jung-Ju; Kang, Hee; Choi, Tae-Young; Lee, Myeong-Soo; Kim, Jong-In
Abstract: Background: Electroacupuncture has been reported to successfully control pain. Currently, no systematic reviews of the effects of electroacupuncture on frozen shoulder patients have been performed. This review aims to provide current evidence on the efficacy of electroacupuncture for the management of pain in frozen shoulder. Methods and analyses: Eleven databases will be searched from their inception: PubMed, AMED, EMBASE, the Cochrane Library, 6 Korean medical databases, and 1 Chinese medical database. Study selection, data extraction, and assessment will be performed independently by 2 researchers. Risk of bias will be assessed using the Cochrane risk of bias assessment tool. Ethics and dissemination: Ethical approvals and patient consent are not required because the meta-analysis will be based on published research. This systematic review will be published in a peer-reviewed journal and disseminated both electronically and in print. The review will be updated to inform and guide health care practice and policy. Trial registration number: PROSPERO 2021 CRD42021247090.